Changes in Reducing Sugar, Fat, Protein, and Sensory Characteristics of Chocolate Bar From The Addition of Clean Fermented Jackfruit Seed Flour - Dian Fitriarni; Irfan Cholid; Ayu Dian Pratiwi Permatahati; Fitriani; Nenengsih Verawati (Journal of Global Sustainable Agriculture, 2025)
This study aims to develop chocolate products with low sugar content by adding jackfruit seed flour. The main ingredients are cocoa powder and jackfruit seed flour. The stages of the study include the stages of making chocolate, adding jackfruit seed flour with concentrations of 5%, 15%, 25% and control. Product analysis includes analysis of water content, ash content, fat content, protein content, reducing sugar content, and product hedonic test. The results of the analysis showed the range of values ​​for each parameter of water content 1,06-2,02%, ash content 1,87-4,48 %, fat content 5,8%-2,02 protein content 5,2-8,6% and reducing sugar content 20,34%-35,4%. The higher the percentage of jackfruit seed flour, the water content did not differ significantly (p>5%), the ash content differed significantly (p<5%) between treatments, the fat content and reducing sugar content showed a decrease. The results of the sensory test showed an average value for the taste and texture of chocolate ranging, aroma 5-7, and overall 4-7 on a scale of 9. Based on the results of the analysis, it can be concluded that jackfruit seed flour can be used as a substitute for chocolate bars with better nutritional and sensory characteristics.